Evaluation of ZIS Management on the Implementation of SIZIPRO System In Improving Transparency and Accountability - Sari, Dewi Puspita; Putra, Yuniarti Hidayah Suyoso (Iqtishodia: Jurnal Ekonomi Syariah, 2024)
Information system implementation is essential for UPZ Baznas Petrokimia Gresik to find out the performance and information needed. The implementation enables administrators to manage the collection and distribution of zakat, infaq, and sadaqah (ZIS) efficiently. This research aims to evaluate the implementation of the SIZIPRO system through SWOT analysis. The method in this research uses a qualitative method with a case study approach to obtain holistic and accurate data. Data is obtained through observation, interviews and documentation. The evaluation is conducted using a SWOT analysis that consists of three stages, namely heuristic evaluation, system usability scale, and concurrent think-aloud. The results showed that the use of the SIZIPRO system was not fully open. However, the system has the potential to improve the existing weaknesses and overcome threats that may occur in ZIS management. Further findings, the management process of the SIZIPRO system implementation can be run in real-time and accurately which enables increased trust and minimizes data errors. The SWOT matrix in this study can be used as a basis for evaluating the use of digital systems in managing the collection and distribution of zakat, infaq, and sadaqah to enhance transparency and accountability.